Student Voices in Teacher Evaluation: The Role of Students in Assessing Student Teachers’ Soft Skills on Asistensi Mengajar Program - Sriyani Mentari; Umi Nuraini; Rizal Palil; Virut Kitnuntaviwat (Universitas Negeri Malang, 2026)
The development of future teachers is not only determined by their mastery of pedagogical competencies, but also by soft skills. However, the evaluation of soft skills in teacher education in Indonesia is still dominated by self, peer, and supervising teacher assessment, while the voices of students are often neglected. This study aims to analyze the differences of soft skills assessment of student teachers participating in the Asistensi Mengajar (AM) program based on a 360-degree feedback approach, as well as to examine the differences between student teachers and students in each dimension of soft skills. This study uses a comparative quantitative design involving 66 student teachers, 198 students, 198 peers, and 66 supervising teachers. Data were collected using a 5-point Likert scale-based soft skills instrument that had been tested for validity and reliability. Data analysis was performed using the Kruskal-Wallis test and Dunn's post hoc test to examine differences between assessor groups (H1), as well as the Wilcoxon Signed-Rank test to compare self-student assessments (H2a–H2d). The results showed a significant difference between the groups of assessors (p < 0.05), particularly between student teachers and students, and between student teachers and their peers. In addition, all dimensions of soft skills showed significant differences between self-assessment and student assessment. Students rated student teachers' communication, problem-solving, and moral attitudes lower, but gave higher scores on adaptability. This study concludes that student voice is a valid and authentic component of evaluation that needs to be integrated into the teacher education assessment system.